Thai Perilla frutescens fruit oil alleviates carbon tetrachloride-induced hepatotoxicities in rats - Narisara Paradee (2020)
© 2020 Wolters Kluwer Medknow Publications. All rights reserved. Objective: To study the effect of perilla fruit oil against carbon tetrachloride (CCl4)-induced liver damage in rats. Methods: Perilla fruit oil was analyzed in terms of fatty acids, tocopherols and tocotrienols using chromatography. Sub-chronic toxicity of perilla fruit oil was investigated in rats for 90 d followed by a 28 d recovery period. Hematological, biochemical and pathological parameters were determined. To evaluate hepatoprotection, rats were divided into five groups and orally administered with Tween 80 for 10 d; Tween 80, silymarin, perilla fruit oil (0.1 mL/200 g) and perilla fruit oil (1 mL/200 g) for 10 d together with subcutaneous injection of CCl4 (2 mL/200 g) on days 9 and 10. Liver enzymes and pathological parameters were determined. Results: Perilla fruit oil contained α-linolenic acid (56.55% of total fatty acid), β-tocopherol (49.50 mg/kg) and γ-tocotrienol (43.65 mg/ kg). Rats showed significant changes in the percentage of monocytes and platelet indices following perilla fruit oil consumption for 90 d; in the percentage of neutrophils and lymphocytes, and RBC indices in the recovery period when compared with the deionized water group. Total protein and creatinine levels were increased while alkaline phosphatase and aspartate aminotransferase levels were decreased (P < 0.05). Organ weight index and pathological indicators did not change significantly. The liver of CCl4-induced rats showed remarkable centrilobular fatty changes, which was ameliorated by perilla fruit oil pretreatment. Aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase levels were decreased (P < 0.05) in rats given perilla fruit oil. Conclusions: Perilla fruit oil is rich in α-linolenic acid, β-tocopherol and γ-tocotrienol and improves blood biomarker levels and protects against CCl4-induced hepatotoxicity. Further studies are required before supporting its use for the treatment of hepatitis.